The Role of the Black Lives Matter Movement in Responding to the Issue of Racism Against Blacks in the United States - Putri Catur Sembadani; Ade Risna Sari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This paper aims to describe the role of the Black Lives Matter Movement in dealing with racism that occurred in the United States from 2013-2022. This writing was analyzed using a research method in the form of descriptive qualitative, where the writer tries to describe or provide an overview with existing words and data to answer the phenomenon regarding the issue of racism that occurred in the United States during the Pre and Post Civil Rights Movement period. The results of writing this article indicate that the Black Lives Matter Movement has succeeded in helping to produce several levels of criminal justice policy reform, such as legislative changes in 10 states in the United States. Policies at every level of the criminal justice system need to be looked at to ensure that they are not harmful to one race or over another.